Comparative study of anthropometric measurement and body composition between soccer players from different competitive levels, elite and sub-elite - B. Masanovic; Z. Milosevic; D. Bjelica (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Background and Study Aim: The purpose of this study was to describe anthropometric characteristics and body composition of soccer players from different competitive levels, elite and sub-elite as well as to make comparison between them. Material and Methods: Seventy-seven subjects were enrolled in this study, divided into three groups: twenty-six elite soccer players, twenty sub-elite soccer players and thirty-one healthy sedentary subjects. All subjects were assessed for anthropometric measurements required for the calculation of body composition variables using standardized procedures which were recommended by previous studies. Data was analyzed by using SPSS and the descriptive statistics were expressed as a mean (SD) for each variable, while the ANOVA and the LSD Post Hoc tests were carried out to discover effects of each type of sport. Results: The results showed that a significant difference was found in weight, body mass index, bone content and body fat, while a significant difference was not found in two remaining variables, height and muscle mass. Conclusions: Therefore, these findings may give coaches from the region better working knowledge and thus provide knowledges for soccer experts which will help them to select talented players as best as possible.